2019
DOI: 10.1177/2151459319841743
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Patient-reported Quality of Life and Pain After a Multidisciplinary Clinical Pathway for Elderly Patients With Hip Fracture: A Retrospective Comparative Cohort Study

Abstract: Introduction: There is an increase in incidence of hip fractures in the ageing population. The implementation of multidisciplinary clinical pathways (MCP) has proven to be effective in improving the care for these frail patients, and MCP tends to be more effective than usual care (UC). The aim of this study was to analyze potential differences in patient-reported outcome among elderly patients with hip fractures who followed MCP versus those who followed UC. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…190 studies underwent full-text review, and 69 studies were selected for final analysis (Figure and eAppendix 3 in the Supplement). Among the final 69 improvement programs, 49 programs significantly decreased TTS and 20 programs did not. Delayed TTS cutoffs were most often defined dichotomously as more than 24 hours, more than 36 hours, more than 48 hours, or more than 72 hours, although some studies collected continuous data.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…190 studies underwent full-text review, and 69 studies were selected for final analysis (Figure and eAppendix 3 in the Supplement). Among the final 69 improvement programs, 49 programs significantly decreased TTS and 20 programs did not. Delayed TTS cutoffs were most often defined dichotomously as more than 24 hours, more than 36 hours, more than 48 hours, or more than 72 hours, although some studies collected continuous data.…”
Section: Resultsmentioning
confidence: 90%
“…190 studies underwent full-text review, and 69 studies were selected for final analysis ( Figure and eAppendix 3 in the Supplement ). 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hip fracture subgroup, two studies found a 14%–54% decrease in the overall in‐hospital post‐operative complication ( p < .01) (Kalmet et al, 2016; Suhm et al, 2014). The post‐operative complications for hip fracture, if reported, were hospital acquired pressure sores (Lau et al, 2010), wound infection (Lau et al, 2010, 2017), blood loss (Malviya et al, 2011), delirium (Kalmet et al, 2016, 2019), pneumonia (Lau et al, 2017) and stroke (Kalmet et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…5 Previous studies have shown that implementation of a standardized multidisciplinary pathway for the treatment of fragility hip fractures in the elderly population improves care and decreases hospital length of stay, postoperative complications, and mortality. [6][7][8] By identifying the mandatory steps between the ER and OR, as well as potential modifiable risk factors, activation of a standardized pathway enables multiple health care providers to work in parallel rather than sequentially to create an efficient, predictable high level of care. The roles of various providers and operational variables that constitute an institutional multidisciplinary hip fracture pathway have been well described in the literature.…”
Section: Introductionmentioning
confidence: 99%